A digital quantum Hall effect - Nicholas, R; Lakrimi, M; Kardynal, B; Khym, S; Mason, N; Rehman, J; Takashina, K; Walker, P; Symons, D; Maude, D; Portal, J (Elsevier, 2000)
The quantum Hall effect in InAs/GaSb heterojunctions at very high fields and low temperatures when both the electrons and holes contribute to the quantized Hall conductance was studied. InAs/GaSb were grown by metal organic vapor phase epitaxy and are known to possess a relatively low level of extrinsic doping so that the majority of charge carriers are created by intrinsic charge transfer from the GaSb layers to the InAs layer. The Hall conductance showed a digital sequence oscillating from 0-1-0 conductance quanta and the diagonal resistivity showed oscillatory insulating behavior due to the formation of a total gap in the energy spectrum.